Clinical Guidelines of the Russian Gastroenterological Association on the Diagnostics and Treatment of Eosinophilic Esophagitis - V. T. Ivashkin; I. V. Maev; A. S. Trukhmanov; T. L. Lapina; D. N. Andreev; E. K. Baranskaya; A. S. Tertychny; S. S. Pirogov; A. A. Sheptulin; D. I. Abdulganieva; D. T. Dicheva; A. V. Zaborovsky; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2019)
Aim. This paper presents guidelines on the diagnostics and treatment of eosinophilic esophagitis, which can be used by practitioners in their everyday practice.Summary. Eosinophilic esophagitis (EoE) is a chronic immune-mediated disease of the esophagus characterized by the symptoms of esophageal dysfunction and a pronounced eosinophilic infiltration of the esophageal mucosa. The EoE diagnostics is based on the clinical manifestations of the disease (dysphagia, food impaction, chest pain regardless of swallowing), as well as on the combination of endoscopic and histological signs. The diagnostic criterion is the eosinophilic infiltration of the esophageal mucosa with an eosinophil density of ≥ 15 per high power field (×400) in at least one of the biopsy specimens (about 60 eosinophils in 1 mm2). Total IgE levels, peripheral blood eosinophilia and skin allergy tests are considered to be additional diagnostic means. Several approaches are used for the treatment of EoE, including proton pump inhibitors (PPIs) and topical glucocorticosteroids (GCS), as well as elimination diets. The choice of therapy should be individualized, with the mandatory assessment of the treatment efficacy after 6–12 weeks using esophagogastroduodenoscopy with biopsy sampling. Endoscopic dilatation should be considered in patients suffering from severe dysphagia due to esophagus stricture.Conclusion. Increased incidence of EoE predominantly among children and young people, as well as its chronic character requiring long-term maintenance therapy, make EoE a significant issue to the practice of gastroenterology.